IMPROVING THE PUBLIC PROCUREMENT SYSTEM: MODERN TRENDS AND MAJOR CHANGES - Ruzimurodova Charos Ural kizi (Labor economics and human capital, 2024)
This article analyzes the current state of the public procurement system, the reforms and current developments being implemented to improve its efficiency, as well as the most important innovations in the public procurement system, including the introduction of digital platforms, online auctions and systems based on blockchain technologies. The results of the study are aimed at increasing the efficiency of public procurement and are aimed at strengthening the economic efficiency, transparency and competitive environment.